1998
DOI: 10.1111/j.1749-6632.1998.tb09748.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Cocaine and Other Drugs: Outcome at Four to Six Yearsa

Abstract: In a longitudinal, prospective study, 95 children born to mothers who used cocaine and other drugs during pregnancy and 75 matched, nonexposed children born to mothers who had no evidence of alcohol or illicit substance use during pregnancy were evaluated for cognitive and behavioral outcome at 6 years of age. Prenatal exposure to cocaine and other drugs had no direct effect on the child's cognitive outcome (measured as IQ), but it had an indirect effect as mediated through the home environment. However, prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 31 publications
4
70
1
2
Order By: Relevance
“…A number of studies have found poor pregnancy and neonatal outcomes among women who used alcohol or illegal drugs during pregnancy, [1][2][3][4] and the long-term impact of prenatal alcohol or illicit drug exposure on the development and behavior of the exposed child [5][6][7][8] is now being documented. However, despite the concern over the consequences of prenatal exposure to alcohol and other drugs, substance use by the pregnant woman remains a frequently missed diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found poor pregnancy and neonatal outcomes among women who used alcohol or illegal drugs during pregnancy, [1][2][3][4] and the long-term impact of prenatal alcohol or illicit drug exposure on the development and behavior of the exposed child [5][6][7][8] is now being documented. However, despite the concern over the consequences of prenatal exposure to alcohol and other drugs, substance use by the pregnant woman remains a frequently missed diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal use of alcohol, tobacco, (Chasnoff et al, 1998). Although the highly publicized phenomenon of "crack babies" might lead one to view prenatal cocaine exposure as a major contributor to the SES disparities noted here, there is little evidence that it plays a role.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 84%
“…Some investigators have found no associations between PDE and cognitive performance, 1,2 play behavior, 3 academic achievement, 2,4 attention, or teacher-rated classroom behavior. 2 In contrast, others have found associations between PDE and behavior problems, 1,5 symptoms of oppositional defiant disorder and ADHD, 6 aggression, 7 task persistence and attention problems, 8,9 and language performance. 10 The inconsistent findings may be partially attributed to methodological inconsistencies and to failure to control for confounders, ranging from prenatal tobacco and alcohol exposure, [11][12][13][14] to parental and family variables, such as mental health, education, intelligence, and income.…”
mentioning
confidence: 90%